A method for beam's eye view breath-hold monitoring during breast volumetric modulated arc therapy. (January 2023) - Carr, Michael A.; Gargett, Maegan; Stanton, Cameron; Zwan, Benjamin; Byrne, Hilary L.; Booth, Jeremy T.
Highlights: First time-resolved chest wall monitoring method for breast volumetric modulated arc therapy. No additional imaging dose needed to monitor the chest wall during treatment. Geometric accuracy within 1 mm when monitoring delivery during dose-critical segments. Abstract: Background and purpose: Deep inspiration breath-hold (DIBH) is a technique that is widely utilised to spare the heart and lungs during breast radiotherapy. In this study, a method was developed to validate directly the intrafraction accuracy of DIBH during breast volumetric modulated arc therapy (VMAT) via internal chest wall (CW) monitoring. Materials and methods: In-house software was developed to automatically extract and compare the treatment position of the CW in cine-mode electronic portal image device (EPID) images with the planned CW position in digitally reconstructed radiographs (DRR) for breast VMAT treatments. Feasibility of this method was established by evaluating the percentage of total dose delivered to the target volume when the CW was sufficiently visible for monitoring. Geometric accuracy of the approach was quantified by applying known displacements to an anthropomorphic thorax phantom. The software was used to evaluate (offline) the geometric treatment accuracy for ten patients treated using real-time position management (RPM)-guided DIBH. Results: The CW could be monitored within the tangential sub-arcs which delivered a median 89% (range 73% to 97%) of the dose to target volume. The phantom measurements showed a geometric accuracy within 1 mm, with visual inspection showing good agreement between the software-derived and user-determined CW positions. For the RPM-guided DIBH treatments, the CW was found to be within ±5 mm of the planned position in 97% of EPID frames in which the CW was visible. Conclusion: An intrafraction monitoring method with sub-millimetre accuracy was successfully developed to validate target positioning during breast VMAT DIBH.